Prayer in Josephus - Jonquière, Tessel M. 1973- (Ancient Judaism and Early Christianity, 2007)
This book is an analysis of prayer in the works of Flavius Josephus. The author discusses both Josephus' views on prayer and his use of prayers within the narrative context. The first part of the book therefore deals with the two passages that Josephus himself wrote on prayer. The second part represents a detailed analysis of 32 prayers selected (mainly) from Antiquitates Judaicae , as to content, context and relation to their source text (if any), revealing the variety of narrative and theological functions that they fulfil. The study also indicates the significance of Josephus' use of terminology derived from the Graeco-Roman world. New light is thus shed on Josephus' historiographic method as well as on his view of God.